Conserved enzymatic production and biological effect of O-acetyl-ADP-ribose by silent information regulator 2-like NAD+-dependent deacetylases. - Borra, M.T.; O'Neill, F.J.; Jackson, M.D.; Marshall, B.; Verdin, E.; Foltz, K.R.; Denu, J.M. (Journal of Biological Chemistry, 2002)
Silent information regulator 2 (Sir2) family of enzymes has been implicated in many cellular processes that include histone deacetylation, gene silencing, chromosomal stability, and aging. Yeast Sir2 and several homologues have been shown to be NAD(+)-dependent histone/protein deacetylases. Previously, it was demonstrated that the yeast enzymes catalyze a unique reaction mechanism in which the cleavage of NAD(+) and the deacetylation of substrate are coupled with the formation of O-acetyl-ADP-ribose, a novel metabolite. We demonstrate that the production of O-acetyl-ADP-ribose is evolutionarily conserved among Sir2-like enzymes from yeast, Drosophila, and human. Also, endogenous yeast Sir2 complex from telomeres was shown to generate O-acetyl-ADP-ribose. By using a quantitative microinjection assay to examine the possible biological function(s) of this newly discovered metabolite, we demonstrate that O-acetyl-ADP-ribose causes a delay/block in oocyte maturation and results in a delay/block in embryo cell division in blastomeres. This effect was mimicked by injection of low nanomolar levels of active enzyme but not with a catalytically impaired mutant, indicating that the enzymatic activity is essential for the observed effects. In cell-free oocyte extracts, we demonstrate the existence of cellular enzymes that can efficiently utilize O-acetyl-ADP-ribose.